Risk assessment for juvenile homicide offenders: est practices and a cautionary note - Fairfax-Columbo, Jaymes (The Routledge international handbook of juvenile homicide, 2024)
Violence and recidivism risk assessment are key components of sentencing for juvenile homicide offenders. Juveniles convicted of homicide face lengthy incarceration up to and including life without possibility of parole. However, sentencing necessarily entails individualized consideration of the juvenile being sentenced to determine, among other things, current and future level of risk posed to the community, examined in the context of desistance. Although the field of violence risk assessment has made great strides in recent decades – particularly via utilization of risk prediction and reduction frameworks such as the Risk-Need-Responsivity model – numerous limitations exist when attempting to predict long-term risk of juvenile offenders. Accordingly, this chapter explores best practices for risk assessment of juveniles; highlights several limitations to the field’s ability to predict long-term risk for juveniles, particularly relevant for the context of juvenile homicide offenders; and discusses a research-informed framework for assessing long-term risk in this population.